Educational Leadership Based on Religious Moderation: Multi-Site Study at Junior High School 1 Atap-Jayapura and Junior High School 1 Praya, Central Lombok - Iwan Fitriani, Mohamad; Andian, Hendy (Tarbawi, 2023)
This research aims to explain the leadership model of school principals in realizing religious moderation at SMP 1 Atap, Jayapura and SMPN 1 Praya, Central Lombok, and compare the leadership models of school principals in the two schools. The research uses a qualitative approach, with a cross-case type of research. Data were collected through interviews, documentation and observation and analyzed throgh steps: 1) using an inductive approach; 2) compiling a conceptual statement; 3) evaluate; 4) recommend; 5) and repeat this process. The research results show that the principal's leadership model in developing religious moderation is a transformational model at SMP 1 Atap Jayapura and a democratic model at SMPN I Praya. There were differences in the moderation idea used. Religious moderation at SMP 1 Atap, Jayapura is based on the perspective of Christian teachings regarding moderation because the majority of teachers and students are Christians, whereas religious moderation at SMPN 1 Praya, Central Lombok is based on the perspective of Islamic teachings because the majority of teachers and students are Muslims. Behind these distinctions, universal ideals such as tolerance, respect for local culture, and nonviolence bind them together.